Active Electric Distribution Network: Applications, Challenges, and Opportunities - Mohd Azmi K.H.; Mohamed Radzi N.A.; Azhar N.A.; Samidi F.S.; Thaqifah Zulkifli I.; Zainal A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric load flow; Electric power distribution; Electric power transmission; Electric power transmission networks; IEEE Standards; Interoperability; Optical fiber communication; Renewable energy resources; Smart power grids; Active distribution network; Active distributions; Communication requirement; Communicationtechnology; Distributed energies; IEEE 802.3 standard; Information and Communication Technologies; Smart grid; Optical fibers